2018
DOI: 10.21307/jofnem-2018-024
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Entomopathogenic Nematode Isolates from the Philippines and their Biological Control Potential Against Lepidopteran Pests of Corn

Abstract: In search for local entomopathogenic nematode (EPN) species as a biological control agent of lepidopterous insect pests of corn, a survey for EPN in the major islands in the Philippines was conducted. Seven EPN populations from 279 soil samples were isolated using Ostrinia furnacalis, the key target insect pest of corn in the country, as bait. Analysis of the ITS1-5.8S-ITS2 ribosomal DNA sequence revealed the presence of Steinernema abbasi, Steinernema minutum, Steinernema tami, and Heterorhabditis indica. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 49 publications
2
14
1
Order By: Relevance
“…From a total of 50 soil samples collected from peanut and grassland areas, only 5 harbored nematodes indicating a recovery rate of 10%. This low recovery rate is congruent with several previous studies on EPNs recovery in different surveys worldwide (Caoili et al 2018 andKour et al 2020). Several abiotic and biotic factors may likely influence the recovery of nematodes in the soil such as soil texture, moisture, pH, and vegetation (Abate et al 2018 andCampos-Herrera et al 2019).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…From a total of 50 soil samples collected from peanut and grassland areas, only 5 harbored nematodes indicating a recovery rate of 10%. This low recovery rate is congruent with several previous studies on EPNs recovery in different surveys worldwide (Caoili et al 2018 andKour et al 2020). Several abiotic and biotic factors may likely influence the recovery of nematodes in the soil such as soil texture, moisture, pH, and vegetation (Abate et al 2018 andCampos-Herrera et al 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Similar result, H. indica, was reported to be very effective against S. litura under laboratory and field conditions (Gokte-Narkhedkar et al 2019). Caoili et al (2018) likewise reported that H. indica (PBCB), an isolate from Luzon island, Philippines, was highly virulent against S. litura, with percentage mean mortality of 88.67%. However, they had a higher LC 50 value (8.89 IJs/larva) at 48 h post inoculation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This result was similar to that reported by Brodie [ 31 ] from Fiji Islands (7.3%), Valadas [ 32 ] from Portugal (6.7%), and Hatting [ 33 ] from South Africa (5%). However, this rate was higher than those reported by Caoili [ 34 ] from the Philippines (2.5%), Majić [ 35 ] from Croatia (2.0%), and Noujeim [ 36 ] from Lebanon (1%). Higher prevalence of EPNs in soil from that determined in the present study was observed by Kanga [ 37 ] from Southern Cameroon (10.4%), Khatri-Chhetri [ 38 ] in Nepal (10.5%), and Malan [ 39 ] in South Africa (17%).…”
Section: Discussioncontrasting
confidence: 64%
“…were recovered from citrus orchards in South Africa (Malan et al ., 2011). Steinernema abbasi, S. minutum, Steinernema tami and H. indica were found to be present in the agricultural and forested areas in the Philippines (Caoili et al ., 2018). Including in the present study, S. siamkayai was isolated from the field and horticulture crops.…”
Section: Discussionmentioning
confidence: 99%